Purwarupa Sistem Peringatan Dini Awan Panas Gunungapi Berbasis Sistem Informasi Geografis (Kasus Gunung Merapi di Perbatasan Jawa Tengah dan Daerah Istimewa Yogyakarta) - M. Nur Budiyanto; P. Insap Santosa; Sujoko Sumaryono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
One of the primary danger that is made by Meraapi mountain volcanic activity is pyroclastic flow which move fast and consists of gas that has a high temperature, volcanic ash and rock. This flow can move quickly down the mountain with a very high temperature. Merapi mountain natural conditions cause difficulties in visual monitoring of pyroclastic flow, whereas the usage of seismic equipment needs experts to analyze the data. This causes difficulties for staffs to warn people early, rapidly and precisely. So that, inspections are needed to plan an early pyroclastic flow warning system and be able to give a danger caution.The research devised an early pyroclastic flow warning based on geographical information system by using thermal sensor as a pyroclastic flow detector,this system is expected to give easiness in monitoring the flow and an early warning to people around Merapi mountain so that it can minimalize victims which is caused by pyroclastic flow. The research was done by surveying, observing and interviewing, whereas designing of the software using waterfall methodology or linear sequence model which consisted of analysis, design, implementation, and testing. Infrared thermal sensor using ATMega8535 microcontroller was used for the testing.The result of the research was a prototype of an early volcano pyroclastic flow warning which is based on geographical information system by utilizing thermal sensor as a pyroclastic flow detector. Thermal sensor used for the system is an infrared thermal sensor using microcontroller as an analog to digital converter. The system has facilities to set the sensor location, read the temperature on each sensor, and give n appropriate condition waning.